Maqianzi (马钱子Strychnos), A poisonous medicinal native to the Western Regions - Yiwen Yang; Baican Yang (Wolters Kluwer Health/LWW, 2019)
Maqianzi (马钱子Strychnos) is also called "Fanmubie (番木鳖)," "Kushi (苦实)" and "QianJi drug (牵机药)." The alias "Fanmubie" shows its origin and its characteristics. The name of "Kushi" implies its taste and flavor. "Qianji Drug vividly shows the clinical manifestations of the poisoning of Maqianzi. The name of "Maqianzi" is the comprehensive display of its characteristic, toxicity, etc., Maqianzi is famous for its poison, which is often used in the treatment of various intractable diseases. It shows the poison Culture in the Western Regions, meanwhile it also displays the unique charm of Traditional herbs in transforming poison into treasure.